Obstructive jaundice and severe pancreatitis due to the foramen of Winslow hernia with multiple anomalies - Bozbulut, Neslihan Ekşi; Akdulum, İsmail and Sarı, Sinan and Özen, İbrahim Onur and Çavuşoğlu, Yusuf Hakan and Boyunağa, Öznur and Dalgıç, Aydın and Dalgıç, Buket (The Turkish Journal of Pediatrics, 2020)
Internal hernia through the foramen of Winslow is a very rare condition, especially in children. Here we report a 16-month-old girl who presented with obstructive jaundice and elevation of pancreatic enzymes and was ultimately diagnosed with internal hernia and malrotation by radiologic investigation and open approach surgery. To the best of our knowledge, obstructive jaundice with pancreatitis and other congenital abnormalities in children with the foramen of Winslow hernia have not been reported previously in the literature.